How competing needs after incarceration lead to adverse health outcomes among people who use criminalized drugs - Catherine Paquette; Kate Ehle; Margaret Roach; Tasia Danns; Katherine LeMasters; Betsy Craft; Lauren Brinkley-Rubinstein (BMC Global and Public Health)
Abstract In the USA, people with a history of criminalized drug use and drug use disorders reentering the community after incarceration frequently experience adverse health outcomes including overdose, suicide, and infectious disease acquisition. This review presents a conceptual model for understanding risk pathways for these outcomes related to post-release psychosocial needs. We first summarize the literature on post-release needs experienced by people who use criminalized drugs during reentry in multiple domains, including basic needs and those related to relationships as well as medical, mental health, and substance use problems. Drawing from a socioecological model, we demonstrate how vulnerability factors related to criminal legal involvement and criminalized drug use operate at intrapersonal (i.e., individual), interpersonal, institutional, community, and policy levels to negatively affect the ability of people who use drugs to meet each of these types of needs. We present research demonstrating that when people leaving incarceration are met with the overwhelming task of addressing competing demands, they often experience strong negative affect, which can lead to risk-conferring behaviors including criminalized drug use. Competing needs also create environmental conditions that amplify risk. We argue for the importance of interventions that address determinants of post-release health at individual and social-environmental levels to prevent adverse outcomes.